Optimization of Vehicle Loading and Unloading Operations by PT. Bandar Krida Jala Patimban - Silvia Agustiar Pamungkas; Elis Suswati (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The purpose of this study is to optimize vehicle loading and unloading operations by PT. Bandar Krida Jala Patimban by knowing the steps taken to overcome obstacles that occur in the yard. The background of this research is the yard conditions and manpower that has not been able to achieve the expected target. The research method used in this study is descriptive with a qualitative approach. The results of the study show that (1) PT. Bandar Krida Jala Patimban is one of the stevedore companies with the least number of incidents at Patimban Port. (2) Loading and unloading operations are carried out in accordance with operational standards to maintain and ensure safety, health and smooth work for workers / man power (3) Obstacles occur due to several factors, namely natural factors, equipment factors, human resource factors, and others. The conclusion of this study recommends the need to hold Operational Standards refreshment activities and competency test training regularly to optimize performance and minimize the occurrence of incidents in the workplace.